Iatrogenic Complications of Compulsory Treatment in a Patient Presenting with an Emotionally Unstable Personality Disorder and Self-Harm. (27th May 2021) - Burrin, Charlotte; Daniels, Natasha Faye; Cardinal, Rudolf N.; Hayhurst, Catherine; Christmas, David; Zimbron, Jorge
Abstract : Attempted suicide and deliberate self-harm are common and challenging presentations in the emergency department. A proportion of these patients refuse interventions and this presents the clinical, legal, and ethical dilemma as to whether treatment should be provided against their will. Multiple factors influence this decision. It is difficult to foresee the multitude and magnitude of complications that can arise once it has been decided to treat individuals who do not consent. This case illustrates a particularly complex chain of events that occurred after treating someone against their will who presented with self-harm and suicidal ideation. These consequences are contrasted with those of not intervening when similar situations arose with the same patient.